Domain III of Bacillus thuringiensis Cry1Ie Toxin Plays an Important Role in Binding to Peritrophic Membrane of Asian Corn Borer. - Dongmei Feng; Zhen Chen; Zhiwen Wang; Chunlu Zhang; Kanglai He; Shuyuan Guo (PLoS ONE, 2015)
The insecticidal IE648 toxin is a truncated Cry1Ie protein with increased toxicity against Asian corn borer (ACB). Cry toxins are pore-forming toxins that disrupt insect midgut cells to kill the larvae. However, the peritrophic membrane (PM) is an important barrier that Cry toxins must cross before binding to midgut cells. Previously, it was shown that Cry toxins are able to bind and accumulate in the PM of several lepidopteran insects. Binding of IE648 toxin to PM of ACB was previously reported and the goal of the current work was the identification of the binding region between Cry1Ie and the PM of ACB. Homologous competition binding assays showed that this interaction was specific. Heterologous competition binding assays performed with different fragments corresponding to domain I, domain II and domain III allowed us to identify that domain III participates in the interaction of IE648 with the PM. Specifically, peptide D3-L8 (corresponding to Cry1Ie toxin residues 607 to 616), located in an exposed loop region of domain III is probably involved in this interaction. Ligand blot assays show that IE648 interact with chitin and PM proteins with sizes of 30, 32 and 80 kDa. The fact that domain III interacts with proteins of similar molecular masses supports that this region of the toxin might be involved in PM interaction. These data provide for the first time the identification of domain III as a putative binding region between PM and 3D-Cry toxin.